(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Study was conducted to compare the effect of full fat soybean and non-fat soybeans meals in broiler diets on their growth performance. A total of one hundred and twenty (120) day old mixed sex chicks purchase from a reputable farm were used for this study, which lasted for eight weeks. The birds were reared on deep litter floor pens using wood shavings as litter material. The birds were brooded in the same pen for two weeks and randomly divided into two (2) groups of 60 birds per group. Data collected were subjected to General Linear Model procedure of the statistics analysis system SAS statistical package. Statistically significant means were compared using Duncan Multiple Range Test (DMRT) Duncan. The results of the experiment carried out on the assessment of weight gain on broiler fed full - fat soybean showed that the final body weight, weight gained, average daily weight gain, total feed intake per bird and feed conversion ratio (FCR) of the birds increases significantly (p<0.01) across the treatments. The final body weight in T3 (4005.00g) was similar to T4 (4140.00g), which were higher than treatment T1 (3510.00) and T2 (3600.00g). The cost price per kg in T3 (47270.75±0.00) N/kg and T4 (7519.06±0.00) N/kg were similar and higher, followed by T2 (6525.84±0.00) N/kg whereas the least cost price per kg was observed in T1 (6360.29±0.00) N/kg. Further studies should be carried out to find other possible ways to influence the real performance of broiler on full fat and non - fat